In Vivo Evaluation of Ligand Targeted Drug Conjugates for Cancer Therapy. Issue 4 (13th September 2018) - Krishnan, Mena Asha; Pandit, Amit; Chelvam, Venkatesh
Abstract: The development of small molecule ligand–targeted therapeutics is currently of paramount importance for treatment of cancer due to their potential to reduce system toxicity and increase potency of a delivered chemotherapeutic drug. The main aim of a targeted drug‐delivery technique is to release the drug cargo selectively into tumor tissues, avoiding off‐site toxicity to healthy tissues and organs during chemotherapy. In this strategy, a chemotherapeutic drug is conjugated to a homing ligand, which has high affinity for proteins over‐expressed on cancer cells, via a peptide linker and a self‐immolative segment that facilitates intracellular release of drug cargo. During development of targeted drug conjugates, preclinical evaluation in tumor models of small animals like mice adds valuable data on the clinical performance of the drug. This article contains a set of protocols for implantation of tumor, determination of optimum dosage required for effective treatment, and estimation of maximum tolerated dose required for any visible side effects during treatment of cancer in tumor models of mice. © 2018 by John Wiley & Sons, Inc.